2018
DOI: 10.1007/s10388-018-0611-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and management of gastric tube cancer after esophagectomy

Abstract: GTCs may occur late in the postoperative course following TEC surgery. If they are discovered at an early stage, these lesions can be cured with ESD. Long-term periodic endoscopic examinations after TEC surgery are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…In our case, we diagnosed the tumor as an advanced cancer, so we decided to perform surgical resection. Gastric tube cancer mostly occurs in the distal region of the gastric tube [12], and the tumor was located near the pyloric ring in our case. Regarding curability, it has been reported that total gastrectomy is necessary for upper gastric tube cancer, but that resection of the distal gastric tube would be sufficient for lower gastric tube cancer [13].…”
Section: Discussionmentioning
confidence: 55%
“…In our case, we diagnosed the tumor as an advanced cancer, so we decided to perform surgical resection. Gastric tube cancer mostly occurs in the distal region of the gastric tube [12], and the tumor was located near the pyloric ring in our case. Regarding curability, it has been reported that total gastrectomy is necessary for upper gastric tube cancer, but that resection of the distal gastric tube would be sufficient for lower gastric tube cancer [13].…”
Section: Discussionmentioning
confidence: 55%
“…Our patient developed the metachronous gastric malignancy relatively early, at about 26 months after the first surgery. Given the wide range of onset of metachronous GTCs, the importance of the annual endoscopic surveillance cannot be overstated, as it allows early detection of potentially curable gastric tube cancers [2,3,6,11].…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology remains uncertain, factors presumably involved in the carcinogenesis are the mediastinal radiotherapy, reflux-induced intestinal metaplasia in vagotomized gastric tubes or Helicobacter pylori [6,13,14]. The choice of therapy should be tailored to the patient and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, preservation of the main trunk of the right gastroepiploic artery (RGEA) and the right gastric artery (RGA) would retain the main blood supply to the reconstructed gastric tube, given that the other gastric vessels were divided during the previous surgery. Several reports have described successful partial resection for early GTC[ 6 , 7 ]. Here, we present a successful case of surgical treatment for GTC and provide details of the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%